Characteristics and recognition of early infections in patients treated with commercial anti‐CD19 CAR‐T cells. (13th October 2021) - Beyar‐Katz, Ofrat; Kikozashvili, Nino; Bar On, Yael; Amit, Odelia; Perry, Chava; Avivi, Irit; Gold, Ronit; Herishanu, Yair; Benyamini, Noam; Duek, Adrian; Ben‐Ami, Ronen; Shasha, David; et al.
Abstract: The characteristics of infections following chimeric antigen receptor T (CAR‐T) cells targeting CD19 in real‐word population are obscure. We analyzed infections' characteristics in the first month among consecutive patients with diffuse large B‐cell lymphoma (DLBCL) (n = 60, median age, 69.3 years), treated with commercial CAR‐T cells. ECOG performance status (PS) was 2‐3 in most patients (58%). Infections were observed in 45% of patients (16, 27%, bacterial infections, and 14, 23%, viral infections). Bacterial infection included clinically documented infection in 7 (Pneumonia, n = 5; periodontal infection, n = 1; and cellulitis, n = 1) and microbiology documented infection (MDI) in 9 patients (Gram‐negative rod, n = 5; Gram‐positive cocci, n = 3, bacteremia; polymicrobial, n = 1). The most common viral infection was cytomegalovirus (CMV) reactivation (n = 10, 17%) leading to initiation of anti‐CMV treatment in 6 (60%) among these patients. None had CMV disease. In univariate analysis, immune effector cell‐associated neurotoxicity syndrome (ICANS) was associated with higher incidence of bacterial infection (OR=4.5, P  = .018), while there was a trend for lower incidence of bacterial infections in patients with chemosensitive disease to bridging therapy (OR=0.375, P  = .074). Age or PS was not associated with increased risk of bacterial infection. Increase in C‐reactive protein (CRP) prior to fever onset was associated with microbiologically documented infections. We conclude that infections are common in the first month following CAR‐T‐cell administration, however, were not increased in elderly patients or those presenting with poorer PS. Increase in CRP prior to fever onset could support infection over cytokine release syndrome.